Gratitude as a Moral Effect That Can Predict the Resilience of Youth - Vera Hasna Salma Syarifah; Anggun Citra Isti’anah; Achmad Sultan Aliuddikri; Zidni Ilmi Rizki (International Conference on Psychology and Education (ICPE), 2023)
In every phase of life, there must be issues or problems. Issues will surely be encountered in both adults and young adults. When people facing their own problems, some people will face it calmly and some people will be anxious and overthink it. The adults have certainly been trained to deal with problems, but not the young generation. Most of them are still not used to dealing with problems yet. Gratitude is one way to face problems to reach resilience. This research exists to explain how gratitude can predict the resilience of youth. This research method used is an approach using a type of research in the form of literature studies. There are three possible points for the conclusions: 1) The relationship between gratitude and youth resilience. Based on previous studies, it may be seen that individuals who have a high gratitude tend to be directly proportional to the level of toughness or severity. 2) How can gratitude be a powerful moral force for the youth. With gratitude, it can build individuals to broaden their view, enhance the quality of life and strengthen social relationships. 3) Implementation of gratitude and consequences. When individuals have adopted an attitude of gratitude, it can make it easier for them to find meaning or lessons in each experience of life.